2009
DOI: 10.7589/0090-3558-45.2.295
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation of Mycobacterium Avium Subsp. Paratuberculosis From Wild Guanacos (Lama Guanicoe) on Tierra Del Fuego Island

Abstract: The aim of this study was to search for Mycobacterium avium subsp. paratuberculosis (Map) infection in a free-ranging wild animal species in a region where Johnes's disease has yet to be reported and to classify Map isolates using a genomic typing method. Fecal samples were obtained from 501 wild guanacos (Lama guanicoe) from Tierra del Fuego Island, Chile, in August 2006. Samples were cultured using Herrold's egg yolk medium with and without mycobactin J. After 9 mo of incubation, suspected Map colonies showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…[164][165][166][167] The organism is shed in the feces of infected animals and may survive on pasture or in lagoons up to a year, especially under cool, moist, acidic conditions. The "bovine" strain appears to be the more common isolate in both wild and domestic camelids, but the ovine strain has been found as well.…”
Section: Nonneoplastic Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…[164][165][166][167] The organism is shed in the feces of infected animals and may survive on pasture or in lagoons up to a year, especially under cool, moist, acidic conditions. The "bovine" strain appears to be the more common isolate in both wild and domestic camelids, but the ovine strain has been found as well.…”
Section: Nonneoplastic Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…In Chile, Map infection has been reported in cattle (Grinbergs and Caorsi 1958), sheep (Zamora et al 1975), goats (Kruze et al 2006), guanacos (Lama guanicoe) (Salgado et al 2009) and hares (Salgado et al 2011 b ). Due to the close relation between wild and domestic animals in some areas, it is suggested that other wild and captive animal populations could be infected Infection by Map has also been described in wild and captive deer populations in many countries (de Lisle et al 1993, Power et al 1993, Fawcett et al 1995, Manning et al 1998, Godfroid et al 2000, Paolicchi et al 2001, Machackova-Kopecna et al 2005, van Kooten et al 2006, Mackintosh et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2010) suggested that ''bison type'' was predominant in deer, wild bison (Bison bison), and other domestic ruminants in India, where 95.1% of domestic livestock was infected with ''bison type.' ' Salgado et al (2009) showed that all isolates from wild guanacos (Lama guanicoe) in Chile were ''cattle type'' and suggested cattle as the primary source of MAP. Here we found that ''cattle type'' was the major genotype of MAP found in wild boar in Korea and suggest that MAP in wild boar may originate from cattle.…”
mentioning
confidence: 99%